Emotional Intelligence and Adjustment Among First-Year University Students - Salsabila Fernanda; N. Rinita; Nisa Amelia; Alviana Chintya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to review the role of emotional intelligence in facilitating first-year university students' adjustment. The transition from high school to college often presents significant psychological, academic, and social challenges. Based on 50 recent academic sources, it was found that students with high emotional intelligence are better able to recognize and regulate emotions, build healthy social relationships, and handle academic pressure adaptively. This study uses a systematic literature review approach with descriptive analysis. The findings indicate that emotional intelligence significantly supports student adjustment success. Therefore, emotional intelligence-based interventions should be considered in university orientation programs.